Parental Role and Student Interests: Impact on Math Learning Outcomes: Peran Orang Tua dan Minat Belajar: Pengaruh pada Hasil Belajar Matematika di Sekolah Dasar - Fanny Arsyatiara; Vevy Liansari (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the relationship between students' perceptions of parental roles, their learning interests, and mathematics learning outcomes in elementary schools. Non-experimental quantitative research methods with a correlational design were employed. Data were collected through questionnaires and documentation, and analyzed using SPSS with multiple correlation and regression tests. The results of the multiple correlation test indicated a non-significant correlation (Sig. F change = 0.705 > 0.05), suggesting no relationship between the variables. Similarly, the multiple regression test revealed that neither the perceived parental role (X1) nor learning interest (X2) had a significant correlation with mathematics learning outcomes (Y), as the t-values (0.710 and 0.430) were smaller than the critical t-value (2.086). The obtained value of R (0.185) fell within the uncorrelated category according to established guidelines. Consequently, it can be concluded that there is no significant relationship between students' perceptions of parental roles and learning interests on mathematics learning outcomes in elementary schools. These findings emphasize the need to explore additional factors that may influence students' academic achievements and to develop targeted interventions to enhance mathematics learning outcomes. Highlights: Study investigated the relationship between parental roles, student interests, and math learning outcomes. Non-experimental quantitative methods were used with correlational design. No significant correlation found between parental roles, student interests, and math learning outcomes in elementary schools. Keywords: Parental Role, Student Interests, Math Learning Outcomes, Elementary Schools, Correlation.